2019
DOI: 10.1039/c9tc02963j
|View full text |Cite
|
Sign up to set email alerts
|

Understanding CrGeTe3: an abnormal phase change material with inverse resistance and density contrast

Abstract: We analyzed the tight Cr clusters in amorphous CrGeTe3 to understand the mechanism of this abnormal phase change material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 57 publications
1
31
0
Order By: Relevance
“…[21] In Figure 5, after labeling the clear diffraction rings in the selected area, the rings corresponding to the (012), ( 014), (003), and (006) planes indicate the R3m structure of Sb at an annealing temperature of 220 C. [22] By increasing the annealing temperature, rhombohedral and orthorhombic GeTe structures were detected, revealing the crystallization of GeTe at 280 C. [23] At 350 C, a new plane appears, which can be labeled as the (0012) plane of rhombohedral CrGeTe. [10] These results indicate that the results are consistent, and both the SAED and XRD results were confirmed.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…[21] In Figure 5, after labeling the clear diffraction rings in the selected area, the rings corresponding to the (012), ( 014), (003), and (006) planes indicate the R3m structure of Sb at an annealing temperature of 220 C. [22] By increasing the annealing temperature, rhombohedral and orthorhombic GeTe structures were detected, revealing the crystallization of GeTe at 280 C. [23] At 350 C, a new plane appears, which can be labeled as the (0012) plane of rhombohedral CrGeTe. [10] These results indicate that the results are consistent, and both the SAED and XRD results were confirmed.…”
Section: Resultssupporting
confidence: 68%
“…[9] The semiconductor Cr 2 Ge 2 Te 6 (CrGT) thin film has been widely studied and used because of its excellent ferromagnetism and unique semiconducting properties. [10] It was observed that CrGT thin film displays an unusual inverse resistance change, exhibiting a high-resistance crystalline reset state and a low-resistance amorphous set state as the temperature increased, and the crystallization temperature was measured to be %276 C. [11] It is also important to mention that CrGT thin films can achieve a fast operation speed of %30 ns, almost as fast as GeTe. [12] Ge-Sb-based materials were observed to exhibit excellent crystallization performance and low power consumption during the operation process.…”
Section: Introductionmentioning
confidence: 99%
“…The vastly different atomic structure and bonding nature lead to distinct electronic transport mechanisms and optical properties that can be utilized in nonvolatile memories (NVM) or neuromorphic computing. The semiconducting amorphous phase usually exhibits relatively high resistance, by at least two orders of magnitude higher than the crystalline ones (exceptions do exist in unconventional PCMs such as Cr 2 Ge 2 Te 6 [84,85] ), and the temperature coefficient of resistivity (TCR) is typically negative due to the large number of charge carriers excited as temperature increases. The resistance difference is partially because the glass usually has 0.2-0.5 eV larger bandgap than the cubic phase.…”
Section: Structure and Bonding Naturementioning
confidence: 99%
“…Cr 2 Ge 2 Te 6 has been reported to exhibit intrinsic ferromagnetism in its 2D crystalline form with a Curie temperature of about 65 K 11 13 . Additionally, reversible phase-change between the amorphous and crystalline phases has been demonstrated for non-volatile phase change memory applications 14 17 . Furthermore, pressure-induced amorphization of Cr 2 Ge 2 Te 6 has been recently reported 18 .…”
Section: Introductionmentioning
confidence: 99%